2010
DOI: 10.1258/td.2009.080376
|View full text |Cite
|
Sign up to set email alerts
|

A profile of dengue cases admitted to a tertiary care hospital in Karnataka, southern India

Abstract: During the past two decades, epidemics of dengue fever have been causing concern in several South-East Asian countries, including India. A study was conducted in a tertiary care hospital situated in Southern India to determine the trends and outcome of dengue cases. There was a steady rise in number of cases from 2002 to 2007, with the largest number of cases seen in 2007. Most cases were observed in the post-monsoon season in the month of September. Out of a total of 344 cases, 285 (82.8%) patients had dengue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The mortality with dengue fever in our study (2.3%) is comparable with the mortality rate due to dengue, in recent studies. [2021]…”
Section: Discussionmentioning
confidence: 99%
“…The mortality with dengue fever in our study (2.3%) is comparable with the mortality rate due to dengue, in recent studies. [2021]…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Kumar et al at Kasturba medical college in 2003, the results found out were similar to this study. 7 The "gold standard "for diagnosis of dengue in a febrile patient is obviously the specific virus detection, virus isolation and virus identification after by cell culture. However, this is gradually being replaced by real time reverse transcriptase polymerase chain reaction (RT-PCR) method for more rapid diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical basis for diagnosing the patients as having Dengue fever was based on WHO criteria like presentation of febrile illness of 2-7 days duration with features like headache, myalgia, arthralgia, rash and/or haemorrhagic manifestations. 6,7…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…antibodies in the patient's blood whereas ELISA is used to differentiate between primary and secondary dengue infections [8]. For rapid diagnosis of the dengue virus, NS1 antigens are detected in the patient's blood [9]. The treatment of the infection is decided on the basis of severity of clinical features and level of fluids in the body.…”
Section: Diagnosis Is Confirmed Upon Detection Of Igm and Iggmentioning
confidence: 99%